2009
DOI: 10.1097/sla.0b013e3181b73126
|View full text |Cite
|
Sign up to set email alerts
|

Portal-Systemic Encephalopathy in a Randomized Controlled Trial of Endoscopic Sclerotherapy Versus Emergency Portacaval Shunt Treatment of Acutely Bleeding Esophageal Varices in Cirrhosis

Abstract: In contrast to EST, EPCS permanently controlled variceal bleeding, resulted in significantly greater long-term survival, and was followed by a relatively low (15%) incidence of PSE. These results were facilitated by rigorous, frequent, and lifelong follow-up that included regular counseling on dietary protein restriction and abstinence from alcohol, and by long-term patency of the portacaval shunt in 98% of patients. Furthermore, these results call into question the practice of avoiding portacaval shunt becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 30 publications
4
40
0
3
Order By: Relevance
“…Portal-systemic encephalopathy (PSE) was quantitated during hospitalization and at each clinic visit by grading four variously weighted components on a scale of 0-4, according to the criteria described in our recent publication. 11 Patency of the SSPCS and grafts from the portal vein or IVC to the right atrium was determined every 1-2 years by Doppler duplex ultrasonography, visceral angiography with pressure measurements, or both. Percutaneous needle liver biopsies were performed every 1-2 years.…”
Section: Portal Decompression Operationsmentioning
confidence: 99%
“…Portal-systemic encephalopathy (PSE) was quantitated during hospitalization and at each clinic visit by grading four variously weighted components on a scale of 0-4, according to the criteria described in our recent publication. 11 Patency of the SSPCS and grafts from the portal vein or IVC to the right atrium was determined every 1-2 years by Doppler duplex ultrasonography, visceral angiography with pressure measurements, or both. Percutaneous needle liver biopsies were performed every 1-2 years.…”
Section: Portal Decompression Operationsmentioning
confidence: 99%
“…Because of the over-riding importance of emergency treatment of variceal bleeding, from 1958 to 2011 we conducted and reported studies of emergency therapy in patients with cirrhosis (Orloff, 1967;Orloff et al, 1980;Orloff et al, 1992); Orloff et al, 1994;Orloff et al, 1995a;Orloff et al, 2009a;Orloff et al, 2009b;Orloff et al, 2011a;Orloff et al, 2011b;Orloff et al, 2010;Orloff et al, 2011c;Orloff et al, 2011d;Orloff et al, 2011e;Orloff et al, 2011f;Orloff et al, 2011g;Orloff et al, 2011h;Orloff et al, 2011i). Our studies have been distinguished by three features that, together, make them different from other reported investigations.…”
Section: Introductionmentioning
confidence: 88%
“…The question is, can cirrhotic patients tolerate an operation of this magnitude when it is performed as an emergency in the face of bleeding? To answer this question, we have conducted prospective studies of emergency PCS (EPCS) over the past 47 years, as follows: (1) an unrandomized study of 400 unselected patients who underwent EPCS; (2) a RCT of EPCS versus emergency medical therapy involving 43 patients at our Veterans Administration Hospital; (3) an unrandomized study of 94 unselected, consecutive patients with Child's class C cirrhosis; (4) a RCT of portacaval shunt versus endoscopic sclerotherapy in 518 unselected patients bleeding from gastric varices; (5) a n u n r a n d o m i z e d s t u d y i n 1 2 p a t i e n t s w i t h u n c o n t r o l l a b l e b l e e d i n g f r o m p o r t a l hypertensive gastropathy; (6) a NIH grant supported RCT of EPCS versus emergency endoscopic sclerotherapy (EST) that enrolled 211 patients who have had more than 10 years of follow-up or until death; and (7) a NIH grant supported RCT of TIPS versus EPCS that enrolled 154 patients who have been followed up for 5-10 years (Orloff, 1967;Orloff et al, 1980;Orloff et al, 1992;Orloff et al, 1994;Orloff et al, 1995a;Orloff et al, 2009a;Orloff et al, 2009b;Orloff et al, 2011a;Orloff et al, 2011b;Orloff et al, 2010;Orloff et al, 2011c;Orloff et al, 2011d;Orloff et al, 2011e;Orloff et al, 2011f;Orloff et al, 2011g;Orloff et al, 2011h;Orloff et al, 2011i;Orloff & Bell, 1983;Bell, et al, 1981;Orloff, 1968;Orloff, 1969;Orloff et al, 1974;Orloff et al, 1975;Orloff & Bell, 1986;Orloff et al, 1995b;Orloff et al, 1997) . The unique features of our studies that, together, make them different from other reported investigations are as follows: (1) EPCS was undertaken within 24 h of initial contact of the patient with our institution in one study and within 8 h in the other six studies; (2) the patients were unselected, which means that all patients with bleeding varices, regardless of their condition ("all comers"), were entered in the studies and treated; (3) the studies were prospective, which means that the p...…”
Section: Emergency Portacaval Shunt For Bleeding Esophageal Varicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our two recent publications [14,15] described our RCT and provided full information on the protocols and methods. These include (1) design of study; (2) patient eligibility; (3) definitions (bleeding esophageal varices (BEV), unselected patients ("all comers"), emergency endoscopic sclerotherapy (EST), long-term endoscopic sclerotherapy (EST), emergency portacaval shunt (EPCS), failure of emergency primary therapy, failure of longterm therapy, rescue therapy, informed consent; (4) randomization; (5) diagnostic work-up; (6) quantitative Child's classification; (7) initial emergency therapy during workup; (8) endoscopic sclerotherapy; (9) emergency portacaval shunt; (10) posttreatment therapy; (11) lifelong follow-up; (12) quantitation of portal-systemic encephalopathy (PSE); (13) data collection.…”
Section: Design Of Randomized Controlled Trialmentioning
confidence: 99%